Redox ratio and optical absorption of polyvalent ions in industrial glasses - W. Thiemsorn (2018)
The changes in glass structure and redox ratio, R (reduced ion to oxidized ion) of Mn2+-Mn3+, Cu+-Cu2+, Cr3+-Cr6+, Ni2+-Ni3+and Co2+-Co3+couples and optical absorption due to Mn3+, Cu2+, Cr3+, Ni2+and Co2+ions in industrial soda-lime-silica glass were investigated as a function of Na2O concentration in the range 11-19 mol%. With increasing Na2O concentration in the experimental glasses, the basicity, expressed as calculated basicity, Λcal, increased.29Si NMR and X-ray diffraction were used to investigate the structural change in glasses. The NMR spectra showed high non-bridging oxygens (NBOs) when the basicity of glass was increased. The results were interpreted to be due to the tetrahedral networks; Q4species were depolymerized by replacing the bridging oxygens (BOs) with NBOs to Q3species. These results confirmed the shift of broadening peaks of XRD patterns. The redox reactions of the Mn2+-Mn3+, Cu+-Cu2+and Cr3+-Cr6+couples shifted more toward their oxidized ions due to the oxygen partial pressure, p(O2), during melting and the oxide ion activity, ao2-, increased with increasing glass basicity. These changes caused the redox ratio of these ion couples to decrease. The Ni2+-Ni3+and Co2+-Co3+couples were assumed to be present only in the Ni2+and Co2+ions in these glasses, respectively. The optical absorption bands due to Mn3+, Cu2+, Cr3+, Ni2+and Co2+ions were also investigated. Their spectra occurred at constant wavelengths with different optical densities or intensities as a function of glass basicity. The increase in the intensities of the absorption bands of these absorbing ions, except for Cr3+ion, at the maximum wavelength, depends not only on the ion concentration but also on the increase of polarizability of oxide (-II) species, αoxide(-II), surrounding the ions. This value affected directly the extinction coefficients of the ions, εion. The increase of εioncaused the colour of glasses appearing in high intensity. In the case of Cr3+ion, the results were reversed such that the lower the concentration, the higher the intensities of colour. © Indian Academy of Sciences.